Water-based adhesive as well as preparation method and application thereof

By using diisocyanate, polyol, chain extender containing disulfide bonds and lipoic acid cross-linked modified polyacrylic acid and other raw materials, the problem of insufficient mechanical strength of existing water-based negative electrode adhesives is solved, high adhesion and self-repair performance are achieved, and the peel strength of the negative electrode of the battery and the electrochemical performance of lithium-ion batteries are significantly improved.

CN119709091AActive Publication Date: 2025-03-28GUANGZHOU HAOYI NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510221084.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The mechanical strength of existing aqueous negative electrode adhesives is insufficient, resulting in their service life in high volume-effect negative electrode materials.

Method used

The aqueous adhesive prepared by diisocyanate, polyol, disulfide bond-containing chain extenders and lipoic acid cross-linked modified polyacrylic acid and other raw materials is formed to form a polyurethane-polyacrylic acid dual-network structure to improve adhesion and self-healing performance.

Benefits of technology

It significantly improves the peel strength of the negative electrode of the battery and the electrochemical performance of the lithium-ion battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709091A_ABST
    Figure CN119709091A_ABST
Patent Text Reader

Abstract

The invention provides a water-based adhesive as well as a preparation method and application thereof. The water-based adhesive is prepared from the following raw materials: diisocyanate, polyol, a chain extender containing disulfide bonds and lipoic acid cross-linked modified polyacrylic acid, the preparation raw materials of the lipoic acid cross-linked modified polyacrylic acid comprise an acrylic acid monomer, an acrylate monomer, a lipoic acid compound and polyethylene glycol diacrylate. The aqueous adhesive provided by the invention has excellent binding power and self-repairing performance, a battery negative electrode prepared from the aqueous adhesive is high in peel strength, and a prepared lithium ion battery is good in electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive materials, and in particular relates to a water-based adhesive and a preparation method and application thereof. Background Art

[0002] As the use of lithium-ion secondary batteries expands, the requirements for improved energy density, reliability and durability are also increasing. As one of the key components of lithium batteries, the performance of the electrode directly determines the battery efficiency and cycle life. Among them, the negative electrode is obtained by coating a slurry made of carbon material and adhesive on the surface of the negative electrode current collector such as copper foil and cutting it into appropriate sizes after drying. As an important raw material for preparing electrodes, the adhesive can bond the active substances to each other and between the active substances and the current collector, thereby preventing the active substances from peeling off from the current collector, thereby ensuring that the entire electrode maintains structural stability during the charge and discharge cycle, and ensuring good electronic pathways and stable electrical performance during battery use.

[0003] Currently commonly used aqueous negative electrode binders such as sodium carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) have a simple structure and insufficient mechanical strength. For negative electrode materials with high volume effect, their service life is far from meeting the standards.

[0004] Therefore, it is necessary to develop a water-based adhesive with high adhesion and self-healing properties. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a water-based adhesive and a preparation method and application thereof. The water-based adhesive has excellent bonding strength and self-repairing properties, and the negative electrode of the battery made with the water-based adhesive has high peel strength, and the prepared lithium-ion battery has good electrochemical properties.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a water-based adhesive, wherein the raw materials for preparing the water-based adhesive include diisocyanate, polyol, a disulfide bond-containing chain extender, and lipoic acid cross-linked modified polyacrylic acid;

[0008] The raw materials for preparing the lipoic acid cross-linked modified polyacrylic acid include acrylic acid monomers, acrylic acid ester monomers, lipoic acid compounds and polyethylene glycol diacrylate.

[0009] In the present invention, the raw materials for preparing the water-based adhesive include diisocyanate, polyol, a chain extender containing a disulfide bond and thioctic acid cross-linked modified polyacrylic acid. The prepared water-based adhesive has a polyurethane-polyacrylic acid double network structure, wherein the functionalized blocks formed by the chain extender containing a disulfide bond and the thioctic acid compound can more effectively improve the mechanical properties of the water-based adhesive, increase elasticity and toughness, and also make it rich in strong dynamic bond effects and chemical bond interactions, thereby giving the water-based adhesive higher bonding strength and self-healing properties.

[0010] Compared with the traditional waterborne polyurethane adhesive, the present invention adopts a more compatible disulfide bond-containing chain extender to replace the carboxylate hydrophilic chain extender, thereby improving the problem that the polyurethane has strong cohesion and weak interaction with the negative electrode active material; and by introducing lipoic acid cross-linked modified polyacrylic acid, it is ensured that its network has strong rigidity and adhesion; the disulfide bond-containing chain extender can start melt polymerization when it reaches 70°C, and can react without adding an organic solvent, which can improve the problem that the use of carboxylate hydrophilic chain extenders in the preparation of traditional waterborne polyurethane adhesives requires the addition of organic solvents to assist the reaction, which is not conducive to environmental protection.

[0011] Preferably, the diisocyanate includes any one of isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (HMDI) or toluene diisocyanate (TDI) or a combination of at least two thereof.

[0012] Preferably, the polyol comprises polyethylene glycol.

[0013] Preferably, the disulfide bond-containing chain extender comprises disulfide diol.

[0014] Preferably, the dithiodiol comprises 2,2'-dithiodiethanol and / or 4,4'-dithiodiylbis(2-methylphenol).

[0015] Preferably, the raw materials for preparing the aqueous adhesive include the following components in parts by weight: 40-60 parts (for example, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts or 58 parts, etc.) of diisocyanate, 60-100 parts (for example, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts or 95 parts, etc.) of polyol, 10-30 parts (for example, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts or 28 parts, etc.) of disulfide bond-containing chain extender and 30-70 parts (for example, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or 65 parts, etc.) of thioctic acid cross-linked modified polyacrylic acid.

[0016] Preferably, the weight proportion of the disulfide bond-containing chain extender in the raw materials for preparing the water-based adhesive is 15 to 25 parts.

[0017] Preferably, the weight proportion of lipoic acid cross-linked modified polyacrylic acid in the raw materials for preparing the water-based adhesive is 40 to 60 parts.

[0018] Preferably, the raw materials for preparing the water-based adhesive further include a tin catalyst.

[0019] Preferably, the tin catalyst includes dibutyltin dilaurate.

[0020] Preferably, the weight portion of the tin catalyst in the raw materials for preparing the aqueous adhesive is 0-1 part (for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part or 0.9 part, etc.).

[0021] Preferably, the raw materials for preparing the water-based adhesive further include a neutralizer.

[0022] Preferably, the neutralizing agent comprises an amine neutralizing agent.

[0023] Preferably, the amine neutralizing agent includes triethylamine and / or N,N-dimethylethanolamine.

[0024] Preferably, the weight proportion of the amine neutralizer in the raw materials for preparing the aqueous adhesive is 1 to 10 parts (eg, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, etc.).

[0025] Preferably, the raw materials for preparing the aqueous adhesive further include water.

[0026] Preferably, the weight proportion of water in the raw material for preparing the aqueous adhesive is 150-250 parts (e.g., 160 parts, 170 parts, 180 parts, 190 parts, 200 parts, 210 parts, 220 parts, 230 parts or 240 parts, etc.).

[0027] Preferably, the raw materials for preparing the thioctic acid cross-linked modified polyacrylic acid include the following components in parts by weight: 30-50 parts (for example, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts or 48 parts, etc.) of acrylic acid monomers, 10-30 parts (for example, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts or 28 parts, etc.) of acrylate monomers, 30-50 parts (for example, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts or 48 parts, etc.) of thioctic acid compounds and 1-10 parts (for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, etc.) of polyethylene glycol diacrylate.

[0028] Preferably, the weight proportion of lipoic acid compounds in the raw materials for preparing the lipoic acid cross-linked modified polyacrylic acid is 35-45 parts.

[0029] Preferably, the acrylic monomer includes acrylic acid and / or methacrylic acid.

[0030] Preferably, the acrylic ester monomer includes hydroxyethyl acrylate and / or 2-phenoxyethyl acrylate.

[0031] Preferably, the lipoic acid compound is lipoic acid and / or a lipoic acid derivative.

[0032] Preferably, the lipoic acid derivative comprises ethylhydroxyphenol-modified lipoic acid.

[0033] Preferably, the raw materials for preparing the lipoic acid cross-linked modified polyacrylic acid further include an ammonium catalyst.

[0034] Preferably, the ammonium catalyst comprises ammonium persulfate.

[0035] Preferably, the weight proportion of the ammonium catalyst in the raw material for preparing the thioctic acid cross-linked modified polyacrylic acid is 0-1 part (e.g., 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part or 0.9 part, etc.).

[0036] Preferably, the lipoic acid cross-linked modified polyacrylic acid is prepared by the following method: acrylic acid monomers, acrylate monomers and ammonium catalysts are mixed for a first reaction, lipoic acid compounds are added for a second reaction, and polyethylene glycol diacrylate is added for a third reaction to obtain the lipoic acid cross-linked modified polyacrylic acid.

[0037] In the present invention, the lipoic acid compound is thermally ring-opened to form lipoic acid compound segments and a cross-linked structure, and polyethylene glycol diacrylate is used for end-capping to inhibit depolymerization and stabilize the structure.

[0038] Preferably, the temperature of the first reaction is 75-85°C (for example, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C or 84°C, etc.), and the time is 2-4 h (for example, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3.0 h, 3.2 h, 3.4 h, 3.6 h or 3.8 h, etc.).

[0039] Preferably, the temperature of the second reaction is 110-130°C (e.g., 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, 126°C or 128°C, etc.), and the time is 0.3-1 h (e.g., 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h or 0.9 h, etc.).

[0040] Preferably, the temperature of the third reaction is 110-130°C (e.g., 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, 126°C or 128°C, etc.), and the time is 0.3-1 h (e.g., 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h or 0.9 h, etc.).

[0041] In a second aspect, the present invention provides a method for preparing the water-based adhesive as described in the first aspect, the preparation method comprising the following steps:

[0042] (1) Diisocyanate and polyol are mixed and reacted to obtain product A.

[0043] (2) The product A obtained in step (1) is mixed with a disulfide bond-containing chain extender, and reacted to obtain a product B.

[0044] (3) The product B obtained in step (2) and thioctic acid cross-linked modified polyacrylic acid are mixed and reacted to obtain the water-based adhesive.

[0045] The aqueous adhesive prepared by the preparation method of the present invention has high structural controllability, and the multi-block structure can improve the bonding defects between negative electrode active materials through functional design, maintain structural stability, improve the problem of insufficient lithium conductivity, and can be used for the bonding of high energy density negative electrode materials; adding thioctic acid cross-linked modified polyacrylic acid to react in step (3) can achieve chain extension and end-capping.

[0046] Preferably, the mixing in step (1) further includes mixing with a tin catalyst.

[0047] Preferably, the reaction in step (1) is carried out under a nitrogen atmosphere.

[0048] Preferably, the reaction temperature in step (1) is 70-80°C (e.g., 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C or 79°C, etc.), and the reaction time is 1.5-2.5 h (e.g., 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h or 2.4 h, etc.).

[0049] Preferably, the reaction temperature in step (2) is 70-80°C (e.g., 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C or 79°C, etc.), and the reaction time is 1-1.5 h (e.g., 1.05 h, 1.1 h, 1.15 h, 1.2 h, 1.25 h, 1.3 h, 1.35 h, 1.4 h or 1.45 h, etc.).

[0050] Preferably, the reaction temperature in step (3) is 75-85°C (e.g., 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C or 84°C, etc.), and the reaction time is 1.5-2.5 h (e.g., 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h or 2.4 h, etc.).

[0051] Preferably, after the reaction in step (3), the steps of adding a neutralizing agent for neutralization and adding water for emulsification are also included.

[0052] Preferably, the neutralization temperature is 20-40°C (for example, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C or 38°C, etc.), and the time is 0.2-1 h (0.3 h, 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h or 0.9 h, etc.).

[0053] In a third aspect, the present invention provides a battery negative electrode, which includes a current collector and a negative electrode material coated on the surface of the current collector; the negative electrode material includes a negative electrode active substance, a conductive agent and the aqueous adhesive as described in the first aspect.

[0054] Preferably, the negative electrode active material includes a silicon-based negative electrode active material.

[0055] Preferably, the conductive agent comprises conductive carbon black.

[0056] In a fourth aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the battery negative electrode as described in the third aspect.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] In the present invention, the aqueous adhesive prepared by using diisocyanate, polyol, disulfide bond-containing chain extender and lipoic acid cross-linked modified polyacrylic acid has excellent bonding force and self-healing performance. The battery negative electrode prepared by using the aqueous adhesive has high peeling strength, and the prepared lithium ion battery has good electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 is the infrared spectrum of the lipoic acid cross-linked modified polyacrylic acid prepared in Example 1;

[0060] Figure 2 is the infrared spectrum of product A obtained in Example 1;

[0061] Figure 3 is the infrared spectrum of product B obtained in Example 1;

[0062] Figure 4is the infrared spectrum of the water-based adhesive prepared in Example 1;

[0063] Figure 5 This is the infrared spectrum of the polyacrylic acid prepared in Comparative Example 1. DETAILED DESCRIPTION

[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0065] The sources of some components in the following examples and comparative examples are as follows:

[0066] Polyethylene glycol diacrylate: The product number is P109708, and the manufacturer is Aladdin.

[0067] Example 1

[0068] The present embodiment provides a water-based adhesive and a preparation method thereof. The raw materials for preparing the water-based adhesive include the following components in parts by weight: 50 parts of diisocyanate (isophorone diisocyanate), 80 parts of polyol (polyethylene glycol 1000), 20 parts of a disulfide bond-containing chain extender (2,2'-dithiodiethanol), 50 parts of thioctic acid cross-linked modified polyacrylic acid, 0.5 parts of a tin catalyst (dibutyltin dilaurate), 5 parts of a neutralizer (N,N-dimethylethanolamine) and 200 parts of water.

[0069] The lipoic acid cross-linked modified polyacrylic acid is prepared by the following method: 40 parts by weight of acrylic acid monomer (acrylic acid), 20 parts by weight of acrylate monomer (2-phenoxyethyl acrylate) and 0.5 parts by weight of ammonium catalyst (ammonium persulfate) are mixed and reacted at 80°C for 3 hours, 40 parts by weight of lipoic acid compound (lipoic acid) are added and reacted at 120°C for 0.5 hours, and 5 parts by weight of polyethylene glycol diacrylate are added and reacted at 120°C for 0.5 hours to obtain the lipoic acid cross-linked modified polyacrylic acid.

[0070] The preparation method of the water-based adhesive comprises the following steps:

[0071] (1) Add diisocyanate, polyol and tin catalyst into a four-necked flask and react at 70 °C for 2 h under nitrogen atmosphere to obtain product A;

[0072] (2) adding a disulfide bond-containing chain extender to the product A obtained in step (1) and reacting at 80° C. for 1 h to obtain product B;

[0073] (3) Add lipoic acid cross-linked modified polyacrylic acid to the product B obtained in step (2) and react at 80° C. for 2 h, then cool to 30° C., add a neutralizer to carry out a neutralization reaction for 0.2 h, and add water to emulsify and disperse the mixture at a stirring speed of 1500 rpm for 0.5 h to obtain the water-based adhesive.

[0074] Example 2

[0075] The present embodiment provides a water-based adhesive and a preparation method thereof. The raw materials for preparing the water-based adhesive include the following components in parts by weight: 40 parts of diisocyanate (dicyclohexylmethane diisocyanate), 70 parts of polyol (polyethylene glycol 1000), 15 parts of a disulfide bond-containing chain extender (2,2'-dithiodiethanol), 40 parts of thioctic acid cross-linked modified polyacrylic acid, 0.5 parts of a tin catalyst (dibutyltin dilaurate), 5 parts of a neutralizer (N,N-dimethylethanolamine) and 200 parts of water.

[0076] The lipoic acid cross-linked modified polyacrylic acid is prepared by the following method: 30 parts by weight of acrylic acid monomer (acrylic acid), 30 parts by weight of acrylate monomer (2-phenoxyethyl acrylate) and 0.5 parts by weight of ammonium catalyst (ammonium persulfate) are mixed and reacted at 85°C for 3 hours, 40 parts by weight of lipoic acid compound (lipoic acid) are added and reacted at 120°C for 0.5 hours, and 10 parts by weight of polyethylene glycol diacrylate are added and reacted at 120°C for 0.5 hours to obtain the lipoic acid cross-linked modified polyacrylic acid.

[0077] The preparation method of the water-based adhesive comprises the following steps:

[0078] (1) Add diisocyanate, polyol and tin catalyst into a four-necked flask and react at 75 °C for 2 h under nitrogen atmosphere to obtain product A;

[0079] (2) adding a disulfide bond-containing chain extender to the product A obtained in step (1) and reacting at 80° C. for 1.2 h to obtain product B;

[0080] (3) Add lipoic acid cross-linked modified polyacrylic acid to the product B obtained in step (2) and react at 70° C. for 2.5 h, then cool to 30° C., add a neutralizer to carry out a neutralization reaction for 0.2 h, and add water to emulsify and disperse the mixture at a stirring speed of 1500 rpm for 0.5 h to obtain the water-based adhesive.

[0081] Example 3

[0082] The present embodiment provides a water-based adhesive and a preparation method thereof. The raw materials for preparing the water-based adhesive include the following components in parts by weight: 40 parts of diisocyanate (toluene diisocyanate), 100 parts of polyol (polyethylene glycol 1000), 20 parts of a disulfide bond-containing chain extender (4,4'-disulfide di(2-methylphenol)), 40 parts of thioctic acid cross-linked modified polyacrylic acid, 0.5 parts of a tin catalyst (dibutyltin dilaurate), 5 parts of a neutralizer (N,N-dimethylethanolamine) and 200 parts of water.

[0083] The lipoic acid cross-linked modified polyacrylic acid is prepared by the following method: 30 parts by weight of acrylic acid monomer (acrylic acid), 30 parts by weight of acrylate monomer (2-phenoxyethyl acrylate) and 0.5 parts by weight of ammonium catalyst (ammonium persulfate) are mixed and reacted at 75°C for 3 hours, 35 parts by weight of lipoic acid compound (lipoic acid) are added and reacted at 120°C for 0.5 hours, and 10 parts by weight of polyethylene glycol diacrylate are added and reacted at 120°C for 0.5 hours to obtain the lipoic acid cross-linked modified polyacrylic acid.

[0084] The preparation method of the water-based adhesive comprises the following steps:

[0085] (1) Add diisocyanate, polyol and tin catalyst into a four-necked flask and react at 80 °C for 2 h under nitrogen atmosphere to obtain product A;

[0086] (2) adding a disulfide bond-containing chain extender to the product A obtained in step (1) and reacting at 80° C. for 1.5 h to obtain product B;

[0087] (3) Add lipoic acid cross-linked modified polyacrylic acid to the product B obtained in step (2) and react at 85° C. for 1.5 h, then cool to 30° C., add a neutralizer to carry out a neutralization reaction for 0.2 h, and add water to emulsify and disperse the mixture at a stirring speed of 1500 rpm for 0.5 h to obtain the water-based adhesive.

[0088] Example 4

[0089] This embodiment provides a water-based adhesive and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the weight fraction of the disulfide bond-containing chain extender (2,2'-dithiodiethanol) is adjusted to 30 parts, and other conditions are the same as those in embodiment 1.

[0090] Example 5

[0091] This embodiment provides a water-based adhesive and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the weight fraction of the disulfide bond-containing chain extender (2,2'-dithiodiethanol) is adjusted to 10 parts, and other conditions are the same as those in embodiment 1.

[0092] Example 6

[0093] This embodiment provides a water-based adhesive and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the weight fraction of lipoic acid cross-linked modified polyacrylic acid is adjusted to 70 parts, and other conditions are the same as those in embodiment 1.

[0094] Example 7

[0095] This embodiment provides a water-based adhesive and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the weight fraction of lipoic acid cross-linked modified polyacrylic acid is adjusted to 30 parts, and other conditions are the same as those in embodiment 1.

[0096] Example 8

[0097] This embodiment provides a water-based adhesive and a preparation method thereof, which is different from Embodiment 1 only in that the weight fraction of thioctic acid compounds (thioctic acid) in the preparation process of thioctic acid cross-linked modified polyacrylic acid is adjusted to 50 parts, and other conditions are the same as those in Embodiment 1.

[0098] Example 9

[0099] This embodiment provides a water-based adhesive and a preparation method thereof, which is different from Embodiment 1 only in that the weight fraction of thioctic acid compounds (thioctic acid) in the preparation process of thioctic acid cross-linked modified polyacrylic acid is adjusted to 30 parts, and other conditions are the same as those in Embodiment 1.

[0100] Comparative Example 1

[0101] This comparative example provides a water-based adhesive and a preparation method thereof, which differs from Example 1 only in that the lipoic acid cross-linked modified polyacrylic acid is replaced with polyacrylic acid of the same mass in the raw materials for preparing the water-based adhesive, and the polyacrylic acid is prepared by the following method: 40 parts by weight of an acrylic acid monomer (acrylic acid), 20 parts by weight of an acrylate monomer (2-phenoxyethyl acrylate) and 0.5 parts by weight of an ammonium catalyst (ammonium persulfate) are mixed and reacted at 80° C. for 3 h, and 5 parts by weight of polyethylene glycol diacrylate are added and reacted at 120° C. for 1 h to obtain the polyacrylic acid, and other conditions are the same as those in Example 1.

[0102] Comparative Example 2

[0103] This comparative example provides a water-based adhesive and a preparation method thereof, which differs from Example 1 only in that the disulfide bond-containing chain extender (2,2'-dithiodiethanol) is replaced with dimethylolpropionic acid of the same mass. The preparation method of the water-based adhesive comprises the following steps:

[0104] (1) Add diisocyanate, polyol and tin catalyst into a four-necked flask and react at 70 °C for 2 h under nitrogen atmosphere to obtain product A;

[0105] (2) adding dimethylolpropionic acid and 20 parts by weight of N-methylpyrrolidone to the product A obtained in step (1), and reacting at 80° C. for 1 h to obtain product B;

[0106] (3) Add lipoic acid cross-linked modified polyacrylic acid to the product B obtained in step (2) and react at 80° C. for 2 h, then cool to 30° C., add a neutralizer to carry out a neutralization reaction for 0.5 h, and add water to emulsify and disperse the mixture at a stirring speed of 1500 rpm for 0.5 h to obtain the water-based adhesive.

[0107] Other conditions are the same as in Example 1.

[0108] Application Example 1

[0109] This application example provides a battery negative electrode, the battery negative electrode comprising a current collector (copper foil) and a negative electrode material coated on the surface of the current collector; the negative electrode material comprises a negative electrode active material (silicon dioxide), a conductive agent (conductive carbon black super P) and the aqueous binder provided in Example 1 in a mass ratio of 9:1:1;

[0110] The battery negative electrode is prepared by the following method: the negative electrode active material, the conductive agent and the aqueous binder provided in Example 1 are mixed, uniformly coated on the surface of the current collector with a coating thickness of 100 μm, and dried to obtain the battery negative electrode.

[0111] Application Examples 2~9

[0112] Application Examples 2 to 9 respectively provide a battery negative electrode, which differs from Application Example 1 only in that the aqueous binder provided in Example 1 is replaced with aqueous binders provided in Examples 2 to 9 of the same mass, and other conditions are the same as those in Application Example 1.

[0113] Comparative Application Examples 1~2

[0114] Comparative Application Examples 1-2 respectively provide a battery negative electrode, which differs from Application Example 1 only in that the aqueous binder provided in Example 1 is replaced with aqueous binders provided in Comparative Examples 1-2 of the same mass, and other conditions are the same as those in Application Example 1.

[0115] The following performance tests were performed on the battery negative electrodes provided in the above Application Examples 1-9 and Comparative Application Examples 1-2.

[0116] (1) Peel strength: The battery negative electrode with 3M tape was peeled off at 180° on a universal tensile testing machine. The width of the tested battery negative electrode was 18 mm, the peeling length was 100 mm, and the peeling speed was 50 mm / min. The peel strength curve was obtained and the average value was taken.

[0117] (2) Electrochemical performance: The battery negative electrode, electrolyte and separator were assembled into a button-type half-cell CR2032 for electrochemical performance testing;

[0118] The electrolyte is prepared by mixing LiPF6, ethylene carbonate (EC) and diethyl carbonate (DEC), wherein the concentration of LiPF6 is 1 mol / L, and the volume ratio of ethylene carbonate to diethyl carbonate is 1:1;

[0119] The above-mentioned diaphragm is a polypropylene diaphragm;

[0120] Electrochemical performance test: The battery cycle performance was tested in the Xinwei charge and discharge system. At 25°C, after standing for 10 hours, it was activated for 3 cycles at a low current density of 0.05A / g, and then a constant current charge and discharge test was performed at a current density of 0.5A / g to obtain the capacity after 100 cycles.

[0121] The test results are shown in Table 1 below:

[0122] Table 1

[0123]

[0124] It can be seen from the contents of Table 1 that the peel strength of the negative electrode of the battery prepared in Application Examples 1 to 9 is ≥3.23N, and the capacity of the button-type half-cell CR2032 prepared after 100 cycles is ≥502.46 mAh / g.

[0125] The number average molecular weight of the aqueous adhesive prepared in Example 1 was 32156 g / mol and the weight average molecular weight was 73513 g / mol as measured by gel permeation chromatography (GPC).

[0126] Figure 1 The infrared spectrum of the lipoic acid cross-linked modified polyacrylic acid prepared in Example 1 is shown in FIG. The lipoic acid cross-linked modified polyacrylic acid has a wave number of 1142 cm -1 The characteristic absorption peak of “-COC-” appeared at the wave number of 1724cm -1 The characteristic absorption peak of "C=O" appears at the wave number of 3400cm -1 A broad characteristic absorption peak of “-OH” appeared at 1600 cm -1 and 1640cm -1 The characteristic peak of aromatic ring appeared at 670 cm -1 The characteristic absorption peak of "-CS-" appeared at , indicating that lipoic acid successfully reacted with other components.

[0127] Figure 2The infrared spectrum of the product A obtained in Example 1 is shown at a wave number of 2200 cm -1 The characteristic absorption peak of "-NCO" appears at the position; after the product A reacts with 2,2'-dithiodiethanol, the infrared spectrum of the generated product B ( Figure 3 ) The characteristic absorption peak of "-NCO" belonging to product A did not appear, indicating that product A and 2,2'-dithiodiethanol successfully reacted to form product B; due to the relatively low content of 2,2'-dithiodiethanol, the content of "-CS-" was low, so Figure 3 There is no "-CS-" absorption peak in the sample.

[0128] Figure 4 The infrared spectrum of the water-based adhesive prepared in Example 1 contains the characteristic absorption peak of "-CS-" of lipoic acid cross-linked modified polyacrylic acid, and the characteristic absorption peak of "-COC" is significantly enhanced, and the water-based adhesive is successfully formed by the reaction; at 3200-3500cm -1 A broad characteristic peak appeared at the site, indicating that there was a strong hydrogen bonding effect.

[0129] Figure 5 This is the infrared spectrum of the polyacrylic acid prepared in Comparative Example 1, wherein lipoic acid was not added for reaction, and no "-CS-" absorption peak appeared.

[0130] Compared with Application Example 1, if the weight fraction of the disulfide bond-containing chain extender in the aqueous adhesive is too high (Application Example 4), the molecular weight of the product B obtained by prepolymerization is too large, resulting in a large hydrogen bond force in the polyurethane network, low adhesion of the prepared battery negative electrode, and reduced electrochemical performance; if the weight fraction of the disulfide bond-containing chain extender in the aqueous adhesive is too low (Application Example 5), the molecular weight of the product B obtained by prepolymerization is low, the adhesion of the battery negative electrode prepared using the aqueous adhesive is low, and the electrochemical performance is reduced. It can be seen that the performance of the aqueous adhesive prepared when the weight fraction of the disulfide bond-containing chain extender in the aqueous adhesive is within a specific range is better.

[0131] Compared with Application Example 1, if the weight percentage of thioctic acid cross-linked modified polyacrylic acid in the aqueous adhesive is too high (Application Example 6), the prepared battery negative electrode has large rigidity, poor elasticity, and reduced electrochemical performance; if the weight percentage of thioctic acid cross-linked modified polyacrylic acid in the aqueous adhesive is too low (Application Example 7), the prepared battery negative electrode has poor self-healing properties, low rigidity, and reduced electrochemical performance. It can be seen that the performance of the aqueous adhesive prepared when the weight percentage of thioctic acid cross-linked modified polyacrylic acid in the aqueous adhesive is within a specific range is better.

[0132] Compared with Application Example 1, if the weight fraction of thioctic acid compounds (thioctic acid) in the preparation process of thioctic acid cross-linked modified polyacrylic acid is too high (Application Example 8), the polymer network in the aqueous adhesive is not rigid enough and is easily deformed due to the volume effect, and the electrochemical performance of the prepared battery negative electrode is reduced; if the weight fraction of thioctic acid compounds (thioctic acid) in the preparation process of thioctic acid cross-linked modified polyacrylic acid is too low (Application Example 9), the self-healing performance is poor, the prepared battery negative electrode has low adhesion, and the electrochemical performance is reduced; it can be seen that the performance of the aqueous adhesive prepared by the weight fraction of thioctic acid compounds in the preparation process of thioctic acid cross-linked modified polyacrylic acid is better within a specific range.

[0133] Compared with Application Example 1, if the lipoic acid cross-linked modified polyacrylic acid is replaced with polyacrylic acid (Comparative Application Example 1), the interaction between polyacrylic acid and polyurethane is low, the adhesion of the prepared battery negative electrode decreases, and the electrochemical performance is significantly reduced.

[0134] Compared with Application Example 1, if the disulfide bond-containing chain extender is replaced with dimethylolpropionic acid (Comparative Application Example 2), the prepared battery negative electrode has low adhesion and reduced electrochemical performance.

[0135] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A water-based adhesive, characterized in that: The raw materials for preparing the water-based adhesive include diisocyanate, polyol, disulfide bond-containing chain extender and lipoic acid cross-linked modified polyacrylic acid; The raw materials for preparing the lipoic acid cross-linked modified polyacrylic acid include acrylic acid monomers, acrylic acid ester monomers, lipoic acid compounds and polyethylene glycol diacrylate.

2. The water-based adhesive according to claim 1, characterized in that The diisocyanate includes any one of isophorone diisocyanate, dicyclohexylmethane diisocyanate or toluene diisocyanate or a combination of at least two thereof; The polyol includes polyethylene glycol; The disulfide bond-containing chain extender includes disulfide diol; The dithiodiol includes 2,2'-dithiodiethanol and / or 4,4'-dithiodiylbis(2-methylphenol).

3. The water-based adhesive according to claim 1, characterized in that: The raw materials for preparing the water-based adhesive include the following components in parts by weight: 40-60 parts of diisocyanate, 60-100 parts of polyol, 10-30 parts of a chain extender containing a disulfide bond, and 30-70 parts of thioctic acid cross-linked modified polyacrylic acid.

4. The water-based adhesive according to claim 1, characterized in that: The raw materials for preparing the water-based adhesive also include a tin catalyst; The tin catalyst includes dibutyltin dilaurate; The weight percentage of the tin catalyst in the raw materials for preparing the water-based adhesive is 0 to 1 part; The raw materials for preparing the water-based adhesive also include a neutralizing agent; The neutralizing agent includes an amine neutralizing agent; The amine neutralizing agent includes triethylamine and / or N,N-dimethylethanolamine; The weight proportion of the amine neutralizer in the raw material for preparing the water-based adhesive is 1 to 10 parts; The raw materials for preparing the water-based adhesive also include water; The weight proportion of water in the raw materials for preparing the water-based adhesive is 150 to 250 parts.

5. The water-based adhesive according to claim 1, characterized in that: The raw materials for preparing the lipoic acid cross-linked modified polyacrylic acid include the following components by weight: 30-50 parts of acrylic acid monomers, 10-30 parts of acrylate monomers, 30-50 parts of lipoic acid compounds and 1-10 parts of polyethylene glycol diacrylate; The acrylic monomers include acrylic acid and / or methacrylic acid; The acrylic acid ester monomers include hydroxyethyl acrylate and / or 2-phenoxyethyl acrylate; The lipoic acid compound lipoic acid and / or lipoic acid derivatives; The lipoic acid derivatives include ethyl hydroxyphenol modified lipoic acid; The raw materials for preparing the lipoic acid cross-linked modified polyacrylic acid also include an ammonium catalyst; The ammonium catalyst includes ammonium persulfate; The weight proportion of the ammonium catalyst in the raw materials for preparing the thioctic acid cross-linked modified polyacrylic acid is 0 to 1 part.

6. The water-based adhesive according to claim 1, characterized in that: The lipoic acid cross-linked modified polyacrylic acid is prepared by the following method: acrylic acid monomers, acrylic acid ester monomers and ammonium catalysts are mixed for a first reaction, lipoic acid compounds are added for a second reaction, and polyethylene glycol diacrylate is added for a third reaction to obtain the lipoic acid cross-linked modified polyacrylic acid; The temperature of the first reaction is 75-85°C and the time is 2-4 h; The temperature of the second reaction is 110-130°C and the time is 0.3-1 h; The temperature of the third reaction is 110-130° C., and the time is 0.3-1 h.

7. A method for preparing a water-based adhesive according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing diisocyanate and polyol, reacting to obtain product A; (2) mixing the product A obtained in step (1) and a disulfide bond-containing chain extender, and reacting them to obtain a product B; (3) The product B obtained in step (2) and thioctic acid cross-linked modified polyacrylic acid are mixed and reacted to obtain the water-based adhesive.

8. The preparation method according to claim 7, characterized in that: The mixing in step (1) further comprises mixing with a tin catalyst; The reaction in step (1) is carried out under a nitrogen atmosphere; The reaction temperature in step (1) is 70-80°C and the reaction time is 1.5-2.5 h; The reaction temperature in step (2) is 70-80°C and the reaction time is 1-1.5 h; The reaction temperature in step (3) is 75-85°C and the reaction time is 1.5-2.5 h; After the reaction in step (3), the steps of adding a neutralizing agent for neutralization and adding water for emulsification are also included; The neutralization temperature is 20-40° C. and the time is 0.2-1 h.

9. A negative electrode of a battery, characterized in that: The battery negative electrode comprises a current collector and a negative electrode material coated on the surface of the current collector; the negative electrode material comprises a negative electrode active material, a conductive agent and an aqueous adhesive as described in any one of claims 1 to 6.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the battery negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of photo-crosslinking dynamic reversible supramolecular polymer adhesive based on lipoic acid small molecular compound

    CN113061263A

  • Metal adhesive composition

    JP2003238326A